KELEKATAN SOSIAL DAN PENGHINDARAN KONFLIK: STUDI PEMILIHAN WARUNG DI KAMPUNG CISAAT - Gita Umul Faizal; Hikma Nadya Rahmah; Ina Elina; Sri Damayanti (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
This study aims to examine the influence of social relationships and conflict avoidance strategies on community consumption practices within a local community. The study employs a qualitative approach using a case study method in Kampung Cisaat, utilizing in-depth interviews, participatory observation, and document analysis. The results indicate that community economic decisions are not entirely based on rational considerations such as price and distance, but are influenced by social factors such as closeness to the seller, neighborhood norms, and the desire to maintain social harmony. The phenomenon of choosing more expensive shops reflects the presence of social embeddedness in economic activities, where economic actions are embedded within existing social relationships. Informal social pressure and solidarity among residents are the primary factors driving the community to continue shopping at specific shops as a strategy to avoid conflict. Thus, the community’s consumption practices demonstrate that economic activities are social in nature and cannot be separated from the context of the social relationships that surround them.